2012
DOI: 10.1159/000336594
|View full text |Cite
|
Sign up to set email alerts
|

Successful Percutaneous Drainage with Iodine Irrigation for Pancreatic Fistulas and Abscesses after Necrotizing Pancreatitis

Abstract: Objective: To report an uncommon method of managing pancreatic fistulas and retroperitoneal abscess. Clinical Presentation and Intervention: A 50-year-old man was admitted with fever, abdominal pain, periumbilical fistula and pus in stool. Five months before admission, he underwent urgent necrosectomy (7 days after onset of pain) and subsequently two more surgeries for necrotizing pancreatitis. Ultrasound revealed fluid collection in the retropancreatic space. After evacuation of pus, contrast medium instilled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Case reports have also described instillation of amphotericin B for a fungal infection of pancreatic collection and use of iodine irrigation in an infected collection. 39,40 The use of streptokinase has also been attempted in order to liquefy and achieve a better drainage of the pancreatic collections, and it was suggested that in comparison to saline treated collections, streptokinase helped in fragmenting the necrosum and changing it's consistency. Surgery could be avoided in the two patients where streptokinase was used.…”
Section: Modifications In Percutaneous Drainage To Improve Outcome Lomentioning
confidence: 99%
“…Case reports have also described instillation of amphotericin B for a fungal infection of pancreatic collection and use of iodine irrigation in an infected collection. 39,40 The use of streptokinase has also been attempted in order to liquefy and achieve a better drainage of the pancreatic collections, and it was suggested that in comparison to saline treated collections, streptokinase helped in fragmenting the necrosum and changing it's consistency. Surgery could be avoided in the two patients where streptokinase was used.…”
Section: Modifications In Percutaneous Drainage To Improve Outcome Lomentioning
confidence: 99%